Enterprise Risk Management pada Risiko Kredit yang dikaitkan dengan Strategi Bisnis di Bank X - , Candra Wahyuni Pitayaningrum ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study discusses the application of enterprise risk management in the credit risk associated with the business strategy of the bank X in the face of the risks that exist. Enterprise risk management itself is a method used for risk management